2004
DOI: 10.1111/j.1945-5100.2004.tb00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration and metamorphism of CO3 chondrites: Evidence from oxygen and carbon isotopes

Abstract: Alteration and metamorphism of CO3 chondrites:Evidence from oxygen and carbon isotopes The results of this study indicate that the oxygen and carbon isotopes in CO3 finds have been significantly disturbed by terrestrial weathering processes. Conclusions based on the isotopic composition of such weathered finds may be significantly flawed. In particular, the Antarctic meteorite ALH A77307 (3.0), suggested as being close in composition to CO-CM chondrite precursor material, has experienced significant terrestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 49 publications
5
78
3
Order By: Relevance
“…The isotopic composition of the purified O gas is then analyzed using a Thermo Fisher MAT 253 dual inlet mass spectrometer (mass resolving power ~200). Analytical precision (1σ) for the system, based on replicate analyses of an internal obsidian standard (n=39) As demonstrated by Greenwood and Franchi (2004), significant shifts in the O isotope composition of Antarctic COs can occur as a consequence of terrestrial weathering. In order, to evaluate the extent of this problem, a subset of primitive COs were leached in a solution of ethanolamine thioglycollate (EATG), which has proved to be efficient at removing terrestrial weathering products from a range of meteorite types, without significantly disturbing their primary O isotope composition (Greenwood et al, 2012 This preparation minimizes the tendency for preferred alignment of platy minerals and allows us to collect random powder diffraction patterns that are representative of the bulk powder.…”
Section: Oxygen Isotope Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The isotopic composition of the purified O gas is then analyzed using a Thermo Fisher MAT 253 dual inlet mass spectrometer (mass resolving power ~200). Analytical precision (1σ) for the system, based on replicate analyses of an internal obsidian standard (n=39) As demonstrated by Greenwood and Franchi (2004), significant shifts in the O isotope composition of Antarctic COs can occur as a consequence of terrestrial weathering. In order, to evaluate the extent of this problem, a subset of primitive COs were leached in a solution of ethanolamine thioglycollate (EATG), which has proved to be efficient at removing terrestrial weathering products from a range of meteorite types, without significantly disturbing their primary O isotope composition (Greenwood et al, 2012 This preparation minimizes the tendency for preferred alignment of platy minerals and allows us to collect random powder diffraction patterns that are representative of the bulk powder.…”
Section: Oxygen Isotope Analysesmentioning
confidence: 99%
“…Position sensitive detector X-ray diffraction (PSD-XRD) has proven to be a very useful tool both for determining bulk mineral abundances and for classification Menzies et al, 2005;Dunn et al, 2010;Howard et al, 2010Howard et al, , 2011Howard et al, 2015). Lastly, bulk O isotopes are an indispensable tool for classifying meteorites and for providing constraints on the influence of fluids during parent body processing (e.g., Clayton and Mayeda, 1999;Young et al, 1999;Greenwood and Franchi, 2004;Schrader et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is also no reason to assume that chondrites classified as type 3 have escaped aqueous alteration. Hydrous minerals are well known in type 3 chondrites like Semarkona (e.g., Hutchison et al 1987), and there is evidence for aqueous alteration in CO chondrites (e.g., Rubin 1998;Greenwood and Franchi 2004;Tomeoka and Itoh 2004).…”
Section: Revision Of the Petrologic Subtypesmentioning
confidence: 99%
“…Several studies have dealt with the determination of the petrographic type by using various proxies as mineralogical associations (Scott and Jones 1990;Chizmadia et al 2002), noble gas and presolar grain content (Newton et al 1992a;Huss et al 2002), organic matter structure, or isotope ratios (Greenwood and Franchi 2004;Bonal et al 2007 and references therein). These studies revealed that Kainsaz has a moderate to intermediate metamorphic grade (3.2 to 3.6) depending on the technique used.…”
Section: Introductionmentioning
confidence: 99%